NAUKA PRAWA W ŻYCIU I DZIAŁALNOŚCI BOHDANA WINIARSKIEGO - Sandorski, Jan (Wydział Prawa i Administracji UAM, 1999)
The article is a biographical record of the course of life and scientific activity of Bohdan Winiarski (1884 - 1969). Reminding the lecturer a character o f Professor Winiarski - the Author emphasises his merits in quality of member of the International Court o f Justice and of the Institute of International Law. He recalls next issues o f interest and personal engagement of this eminent expert in international law - not only as a jurist but also as a politician (among others - armed conflict between the Soviet Union and Finland is here recalled). Drawing briefly up the vicissitudes of Winiarski, the Author cites chronologically his successive achievements, most important publications and opinions on the then virtual legal problems of international nature. Largely are also discusses opinions of Winiarski on didactic matters of international law with emphasis laid on the attention which Winiarski had attached to defence of interests of the Polish nation under difficult circumstances of the period between the two world wars (and more especially - against the background of growing conflict between Germany and Russia during thirties).
THE SCIENCE OF LAW IN THE COURSE OF LIFE AND ACTIVITY OF BOHDAN WINIARSKI